Klima, Landschaft, Eingriffe und Bauleitplanung: Ausgewählte Fach- und Rechtsfragen - Mitschang, Stephan (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The conference proceedings contain the written presentations of a scientific symposium held in September 2022 at the Technical University of Berlin with the topic "Climate, Landscape, Interventions and Land Use Planning". It includes contributions on climate protection and its role in connection with landscape planning, encroachment management and species protection measures. Furthermore, maintenance measures, objects of the preliminary examination, the latest developments in environmental protection law and supreme court rulings are discussed. Three practical reports from the local and regional planning level will deepen different aspects.With contributions by Dr. Andreas Decker | Prof. Dr. Annette Guckelberger | Prof. Dr. Stefan Heiland | Dr. Henning Jaeger | Johannes Mayer | Univ.-Prof. Dr. Stephan Mitschang | Dr. Wolfgang Patzelt | Prof. Dr. Olaf Reidt | Prof. Dr. Alexander Schink | Mareike Schnorr | Dr. -Ing. Tim Schwarz | Anke Sterz